Verbal cluster order and processing complexity. (March 2017) - Bloem, Jelke; Versloot, Arjen; Weerman, Fred
Abstract: We examine a case of word order variation where speakers choose between two near-synonymous constructions partly on the basis of the processing complexity of the construction and its context. When producing two-verb clusters in Dutch, a speaker can choose between two word orders. Previous corpus studies have shown that a wide range of factors are associated with this word order variation. We conducted a large-scale corpus study in order to discover what these factors have in common. The underlying generalization appears to be processing complexity: we show that a variety of factors that are related to verbal cluster word order, can also be related to the processing complexity of the cluster's context. This implies that one of the word orders might be easier to process — when processing load is high, speakers will go for the easier option. Therefore, we also investigate which of the two word orders might be easier to process. By testing for associations with factors indicating a higher or lower processing complexity of the verb and its context, we find evidence for the hypothesis that the word order where the main verb comes last is easier to process. Highlights: Speakers may choose to produce the order that is easiest to process when faced with free word order variation. Minimizing processing complexity plays an important role in Dutch verb cluster word ordering. In Dutch verb clusters, the participial-final word order is easier to process. Large, automatically annotated syntactic corpora enable more detailed study of grammatical variation phenomena.